Analisis Kestabilan Lereng dan Penanganan Longsor Area Puncak Pass Cianjur STA 20+650, Jawa Barat Menggunakan Program Plaxis - Meiprastyo, Xbal; Rono IS Rono Hadinagoro; Andhika Mahdi Arifi; Rizal Zulfikar (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
Puncak Pass STA. 20+650, it’s a hills area with land use change condition but there’s no different or change topography. The main causes landslide in Puncak Pass. There’s assessment like building and street in the top of slope that causes a bigger landslide it even hapen twice. There’s a lot of causes impact like break the highway and collapsed building. This study task is about handling the landslide with such condition finite element method analysys and plaxis program for analysys the deformation geotechnic stabilition in analysys handing landslide. There’s a secure system on the analysys results (Msf) 1,112. The results of analysys of ten safety factors with gabion dan pile combination 1,845 in normal condition, if there’s earthquake the safety factor will touch 1,244. Recommendations for a landslide in Pucak Pass area is combinations of gabion and pile that meets the design criteria.